2018
DOI: 10.1111/jocn.14205
|View full text |Cite
|
Sign up to set email alerts
|

The third person in the room: The needs of care partners of older people in home care services—A systematic review from a person‐centred perspective

Abstract: The carers in home care services need competence to identify and meet the needs of care partners. The implementation of person-centred values in home care services can contribute to meet the needs of care partners to a greater extent than today. Future research on the needs of care partners of older people with mental health problems needs to be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 44 publications
0
53
0
3
Order By: Relevance
“…Patient-and family-centred care must involve collaboration with patients, families and care providers. [38,39] Care plans for patients with complex or multiple chronic conditions should consider caregivers' needs and incorporate their input given the impact of caregiving on their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-and family-centred care must involve collaboration with patients, families and care providers. [38,39] Care plans for patients with complex or multiple chronic conditions should consider caregivers' needs and incorporate their input given the impact of caregiving on their lives.…”
Section: Discussionmentioning
confidence: 99%
“…When older people with mental health problems are treated as a low priority group, it is reasonable to believe that this will also have a negative impact on their care partners. Other studies conclude that care partners have several, continuously unmet needs, and there is a lack of support from the municipal health services in meeting these needs (Anker-Hansen et al, 2017;Wester, Larsson, Olofsson, & Pennbrant, 2013).…”
Section: Mental Healthmentioning
confidence: 99%
“…The experiences and needs of care partners have been widely studied over the last few decades (Barnes, Given, & Given, ; Thomas, Morris, & Harman, ; Tønnessen, ; etc.). In an earlier systematic review, however, we reported that, despite extensive research on care partner's needs, care partners still have several unmet needs, ranging from practical help, like information and training, to emotional support (Anker‐Hansen, McCormack, Skovdahl, & Tønnessen, ). Furthermore, we reported the lack of research on the care partners of older people with mental health problems who receive home care services.…”
Section: Introductionmentioning
confidence: 99%
“…Health care is often first offered when a somatic disease occurs, which means that care partners may have provided care for years without help. When home care services initiate health care, the mental health needs of the person are often not prioritised and thus remain the care partners’ responsibility. When these persons get insufficient help, this also affects their care partners .…”
Section: Introductionmentioning
confidence: 99%
“…When home care services initiate health care, the mental health needs of the person are often not prioritised and thus remain the care partners’ responsibility. When these persons get insufficient help, this also affects their care partners . The relationship between formal and informal care has been conceptualised in different ways , conventionally in a perspective about how professionally registered carers (home care staff) and un‐registered carers (the care partners) collaborate in meeting needs, clarifying roles and agreeing responsibilities .…”
Section: Introductionmentioning
confidence: 99%